Operating systems incorporating UNIX and Windows - Ritchie, C. Colin Ritchie (Australia: Thomson, 2003)
This edition provides the practical course text to the Operating Systems required by the majority of degree and HND courses in Computing. It uses as a basis the familiar operating systems of UNIX, MSDOS and Windows. Colin Ritchie provides a clear introduction of all the terminology and concepts involved, and enables the reader to gain a thorough knowledge of the subject by blending technical discussion with real-practice issues, supported by practical exercises.
Includes bibliography, index and web references
Keywords: Operating Systems -- Computers; UNIX -- Computer file; Microsoft Windows -- Computer File; Windows